A Simulation Study of the Use of Vaccination to Control Foot-and-Mouth Disease Outbreaks Across Australia - Capon, Tim R.; Garner, Michael G.; Tapsuwan, Sorada; Roche, Sharon; Breed, Andrew C.; Liu, Shuang; Miller, Corissa; Bradhurst, Richard; Hamilton, Sam (Frontiers in Veterinary Science, 2021)
This study examines the potential for foot-and-mouth disease (FMD) control strategies that incorporate vaccination to manage FMD spread for a range of incursion scenarios across Australia. Stakeholder consultation was used to formulate control strategies and incursion scenarios to ensure relevance to the diverse range of Australian livestock production regions and management systems. The Australian Animal Disease Spread model (AADIS) was used to compare nine control strategies for thirteen incursion scenarios, including seven control strategies incorporating vaccination. The control strategies with vaccination differed in terms of their approaches for targeting areas and species. These strategies are compared with two benchmark strategies based on stamping out only. Outbreak size and duration were compared in terms of the total number of infected premises, the duration of the control stage of an FMD outbreak, and the number of vaccinated animals. The three key findings from this analysis are: 1) smaller outbreaks can be effectively managed by stamping out without vaccination; 2) the size and duration of larger outbreaks can be significantly reduced when vaccination is used, and 3) different vaccination strategies produced similar reductions in the size and duration of an outbreak, but the number of animals vaccinated varied. Under current international standards for regaining FMD-free status, vaccinated animals need to be removed from the population at the end of the outbreak to minimise trade impacts. We have shown that selective, targeted vaccination strategies could achieve effective FMD control whilst significantly reducing the number of animals vaccinated.